THE EFFECT OF SPECIFIC EXERCISES ON AGILITY, MOTOR SPEED, AND SKILL PERFORMANCE OF UNDER-19 FOOTBALL PLAYERS - Jaafar Abd Abu Althar Abd (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The applicability of the importance of this research is that the specific exercises are an imitation of the performance that is closer to the real one in football matches in terms of the difficulty of its execution. In addition, it is also performed in a competitive environment, so the player has the opportunity to express his competitiveness and make the most of the time and opportunity available to him to perform a fast and accurate response at the level of motor performance and skill performance to defeat his competitor and with fluidity and coordination and accuracy and perfection in technical execution. Objectives. The objectives of this research are: To determine the impact of specific exercises in developing agility, motor speed, and skill performance among under-19 players. Method. The researcher used the experimental method because it is the most appropriate method in light of the research problem. The research population included clubs of Wasit Governorate that participated in the Youth League for the season 2024–2025, and it included 127 players. The researcher designed and implemented specialized football-specific exercises for the experimental group and the control group in accordance with the program of the coach. Results. Each of the specific exercises included complete rest periods between repetitions, so that each athlete completely recovered his energy to be able to perform the next repetition without the fatigue that may not allow him to maintain the level of execution quality. So the results of the previous exercise, although they were still present, would not be a limiting factor in the next repetition or in the other exercises. After completing the pre-test and post-test, the researcher used the Statistical Package for the Social Sciences (SPSS) program to analyze the data and draw the results. Conclusion. The researcher concluded that the specific exercises were appropriate for the experimental group and can be applied to all the research population. The relationship between motor abilities and technical abilities improves actual performance on the ground. The specific exercises implemented by the experimental group, where it combined agility, balance and football skills had a huge impact in developing agility and motor speed.